Social Determinants of Mental Health in People with Disabilities: A Reflective Commentary - Manil Raj Maharjan, (Journal of Development Review, 2025)
Mental health is integral to overall well-being. Approximately 16% of the global population experiences disability, facing higher rates of mental health challenges exacerbated by social determinants such as income disparity, social exclusion, and limited access to education and healthcare. The essay explores these determinants in relation to People with Disabilities (PWDs), highlighting the inadequate mental health services available for this group. Social and cultural stigmas surrounding mental health issues further complicate the situation, leading to discrimination and decreased access to necessary services. The social model of disability underlines that disability results more from structural barriers than individual impairments, suggesting that mental health professionals and policymakers should address these systemic issues. The paper advocates for developing inclusive, accessible mental health resources that consider the unique experiences of PWDs while integrating their voices into policymaking processes. Drawing from personal experience as a PWD and mental health counselor, the author expresses a commitment to improving mental health services for PWDs in Nepal, emphasizing the need for collaboration with government and organizations representing individuals with disabilities. By recognizing and addressing the social determinants affecting PWDs' mental health, the goal is to foster an equitable support system that improves mental well-being and life outcomes for this marginalized group.